The Emergence of SARS-CoV-2 Variants With a Lower Antibody Response: A Genomic and Clinical Perspective - Biswas, Suvro; Mahmud, Shafi; Mita, Mohasana Akter; Afrose, Shamima; Hasan, Md. Robiul; Paul, Gobindo Kumar; Shimu, Mst. Sharmin Sultana; Uddin, Md. Salah; Zaman, Shahriar; Park, Moon Nyeo; Siyadatpanah, Abolghasem; Obaidullah, Ahmad J.; et al. (Frontiers in Medicine, 2022)
The emergence of several novel SARS-CoV-2 variants regarded as VOCs or variant of concern, have exacerbated pathogenic and immunologic prominences as well as reduced diagnostic sensitivity due to phenotype modification capable mutations. Additionally, latent, more virulent strains that have emerged from unique mutations due to greater evolutionary potential pose a threat to vaccine effectiveness in terms of upcoming and existing variants. As a result, resisting natural immunity, which leads to higher reinfection rates, and avoiding vaccination-induced immunization, which leads to a lack of vaccine effectiveness, has become a crucial concern for public health around the world. This paper attempts to review the genomic variation and pandemic impact of emerging variations of concern based on clinical characteristics management and immunization effectiveness. The goal of this paper is to have a better knowledge of the relationship between genome level variation, clinical symptom demonstration, and current vaccination in the instance of VOCs.